Toward the development of a Preparedness and Response Protocol for epidemics and pandemics - de Oliveira, Fabíola Negreiros; Eckhardt, Daniel; Leiras, Adriana; Gonçalves, Paulo; de Brito, Irineu [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida; Pedroso, Frederico Ferreira (FapUNIFESP (SciELO), 2023)
Paper aims: The paper aims to analyze preparedness and response for epidemics and pandemics, taking as reference the COVID-19 pandemic, to provide a foundation for developing a preparedness and response protocol to guide Civil Defenses fighting against health threats. For this purpose, we present the results of interviews carried out with Brazilian Civil Defenses, evaluating the role and the type of responsibility (in charge or supportive) of 12 entities in four key areas: (i) awareness and training; (ii) surveillance; (iii) information and communication; (iv) logistics and supplies. Originality: The role of Civil Defenses in health threats still needs to be explored in academia. We often see Civil Defenses working to reduce risks and damages suffered by the population in case of disasters such as floods, landslides, and fires. In this paper, we go deeper into Civil Defense’s role and show that its efforts can be headed to face biological disasters such as the COVID-19 pandemic. In this sense, the paper is original as it brings an innovative outlook on the role of Civil Defense, providing inputs for developing a preparedness and response protocol for epidemics and pandemics. Research method: We analyze 12 Brazilian Civil Defenses from different States in Brazil. The results were gathered through 9 interviews via video call and three responses from a questionnaire that guided the interviews. We evaluated data from Civil Defenses individually, and then using content analysis, we categorized the data to structure the results and raise essential insights. Main findings: Most of the actions taken by the Civil Defenses during the pandemic response included logistics-related activities such as storage, transportation, distribution of required supplies, and mobilization of supply operations. Implications for theory and practice: The findings emphasize the capacity of Civil Defenses to act in a vast scope of disasters, including biological disasters. Also, this study helps practitioners to develop guidelines and protocols to support Civil Defense in preparedness and response activities to epidemics and pandemics.
Keywords: Civil Defense; COVID-19; Pandemics; Preparedness; Response